BIPA Learning Design Based On Buginese Culture - Arisnawati, Nurlina; Yulianti, Andi Indah; Rahmatiah, Rahmatiah (ETDC: Indonesian Journal of Research and Educational Review, 2022)
Learning and studying a language are essentially learning and examining its culture because language activities are also considered an activity to convey cultural messages to the community. Learning BIPA is a significant and prospective field in introducing a language and its culture. This research aims to develop the contextual BIPA (Bahasa Indonesia bagi Penutur Asing) teaching materials based on the local culture: Bugis culture. The fundamental concept of this research is research and development (R&D). This teaching material is based on the local culture of South Sulawesi, especially related to weddings and traditional South Sulawesi snacks such as Barongko. The goal is to learn the Indonesian language and introduce the Bugis culture, such as Bugis traditional marriage, which has several stages and each of which has its own ritual. Likewise, the traditional snacks topic aims to introduce South Sulawesi traditional snacks. The students are expected to be communicative and master some vocabulary and terms related to the Bugis culture based on the discourse’s explanation of this learning material.